Mechanosensing biology - Noda, Masaki; SpringerLink (Online service). (Tokyo, Japan Springer, 2011)
Mechanical stress is vital to the functioning of the body, especially for tissues such as bone, muscle, heart, and vessels. It is well known that astronauts and bedridden patients suffer muscle and bone loss from lack of use. Even the heart, in pumping blood, causes mechanical stress to itself and to vascular tissue. With the loss of mechanical stress, homeostasis becomes impaired and leads to pathological conditions such as osteopenia, muscle atrophy, and vascular tissue dysfunction. In elderly populations, such mechanical pathophysiology, as well as the mechanical activities of locomotor and cardiovascular systems, is important because skeletal and heart functions decline and cause diseases in other organs. In this monograph, mechanical stress is discussed by experts in the field with respect to molecular, cellular, and tissue aspects in relation to medicine. Covering topics such as gravity and tissues and disuse osteoporosis, the book provides the most up-to-date information on cutting-edge advancements in the field of mechanobiology and is a timely contribution to research into locomotor and circulatory diseases that are major problems in contemporary society.
Part I Cells and Signals. -1. Nanotechnology in Mechanobiology: Mechanical Manipulation of Cells and Organelle While Monitoring Intracellular Signaling. -2.Molecular Mechanisms Underlying Mechanosensing in Vascular Biology. 3.Mechanobiology During Vertebrate Organ Development. Part II Tissue and Gravity. -4. Mechanobiology in Skeletal Muscle: Conversion of Mechanical Information into Molecular Signal. -5. Mechanobiology in Space. -6. Mechanical Stress and Bone. -7. TRP Channels and Mechanical Signals. Part III Skeletal Response. -8. Osteoblast Biology and Mechanosensing. -9. Osteocytes in Mechanosensing: Insights from Mouse Models and Human Patients. -10. Osteocyte Mechanosensation and Transduction. -11. Mechanosensing and Signaling Crosstalks. -12.Osteoblast Development in Bone Loss Due to Skeletal Unloading. Part IV Bone Signaling. -13. Mechanosensing in Bone and the Role of Glutamate Signalling. -14. Osteoclast Biology and Mechanosensing
College of Science Library has electronic copy. Kindly send us a message through cslib@science.upd.edu.ph using your UP mail for the copy of this material.
Electronic reproduction.
Keywords: Biomechanics; Biosensors; Electronic books